Magnetic reconnection and current sheets in 2D and 3D magnetic configurations - Frank, A.G.; Bogdanov, S.Yu.; Kyrie, N.P.; Markov, V.S. (Вопросы атомной науки и техники, 2000)
Experimental results are presented on the study magnetic reconnection phenomena and current sheet formation and evolution in 2D and 3D magnetic configurations with some topological singularities: null-lines, null points, singular lines. Current sheet evolution in 2D fields with null-lines manifests qualitative agreement with principal features of flare-type phenomena. Current sheet formation was revealed to occur in various 3D magnetic configurations, both with and without isolated magnetic null-points, specifically in agnetic configurations with Xlines. Results demonstrate self-organization of current sheets to be a general process for plasma dynamics in nonuniform magnetic fields.